2017
DOI: 10.22373/jppm.v1i1.1734
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Problem Based Learning Untuk Meningkatkan Kemampuan Komunikasi Matematis Dalam Pemecahan Masalah Di Kelas Ix-6 SMPN 8 Banda Aceh

Abstract: The background of this study is the low level-achievement of students’ mathematical communication in solving problems of students grade 9 (Classroom IX-6), SMP Negeri 8 Banda Aceh. The results of the pre-test showed that 60% students only write the given information, 52% students only write the asking-problems, 4% students successfully make model/mathematical representation, 80% students write the formulas, 100% students write calculating operation, 72% students solve problems in well ordering and 64% studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…The results of research conducted by Duskri et al (2017), showed mathematical communication skills of students in the first cycle reached 60% completeness then in the second cycle increased to 95.83%. The way to apply PBL models in class IX-6 Banda Aceh 8 Middle School that can improve mathematical communication skills is to apply according to the PBL model phase to give contextual problems and in accordance with the real world of students, guide the mathematical communication steps that appear in each LKPD, and give a real appreciation to every student who asks or responds to questions.…”
Section: Discussionmentioning
confidence: 97%
“…The results of research conducted by Duskri et al (2017), showed mathematical communication skills of students in the first cycle reached 60% completeness then in the second cycle increased to 95.83%. The way to apply PBL models in class IX-6 Banda Aceh 8 Middle School that can improve mathematical communication skills is to apply according to the PBL model phase to give contextual problems and in accordance with the real world of students, guide the mathematical communication steps that appear in each LKPD, and give a real appreciation to every student who asks or responds to questions.…”
Section: Discussionmentioning
confidence: 97%
“…Demikian pula dengan penelitian oleh (Duskri et al, 2017) yang mengemukakan bahwa kemampuan komunikasi matematis siswa mengalami peningkatan menjadi 95,83% tuntas pada siklus II dengan pemberian penegasan dan bimbingan dalam LKPD dan pemberian penghargaan kepada siswa yang merespon pertanyaan. Selanjutnya, penelitian yang dilakukan oleh (Kadir, 2020)…”
Section: Peningkatan Kemampuan Komunikasi Matematis Siswa Pada Kedua ...unclassified
“…Dan kelima, menganalisis dan mengevaluasi proses pemecahan masalah. Tahapan ini merupakan refleksi setelah melaksanakan pembelajaran berbasis masalah Model PBL juga dapat meningkatkan komunikasi matematika dan pemecahan masalah (Duskri, Maidiyah, Risnawati & Ilham, 2017), bahkan model PBL dapat meningkatkan komunikasi matematika dan kepercayaan diri siswa (Kumala, Waluyo & Siswanto, 2019).…”
Section: Pendahuluanunclassified